Open innovation in neuroscience research and drug discovery - Hunter, A; Lee, W; Bountra, C (SAGE Publications, 2018)
The pressures on the pharmaceutical industry have incentivised a number of new collaborative models of research and development which can be categorised as open innovation. Examples of the different types of models employed are discussed and some, but not all, of these have been used to promote research and drug discovery for central nervous system disorders. Some are completely open access, while others have some intellectual property restrictions. Going forward, more ways of promoting open innovation and the sharing of best practice, especially in the neurosciences, will stimulate research and hopefully accelerate new medicines development.